Assessment of Venous Thrombosis in Animal Models. Issue 2 (February 2016) - Grover, Steven P.; Evans, Colin E.; Patel, Ashish S.; Modarai, Bijan; Saha, Prakash; Smith, Alberto
Abstract : Deep vein thrombosis and common complications, including pulmonary embolism and post-thrombotic syndrome, represent a major source of morbidity and mortality worldwide. Experimental models of venous thrombosis have provided considerable insight into the cellular and molecular mechanisms that regulate thrombus formation and subsequent resolution. Here, we critically appraise the ex vivo and in vivo techniques used to assess venous thrombosis in these models. Particular attention is paid to imaging modalities, including magnetic resonance imaging, micro–computed tomography, and high-frequency ultrasound that facilitate longitudinal assessment of thrombus size and composition.